Freie Wahl – das Projekt bestimmt die Planungsmethode. Issue 12 (22nd November 2019) - Scheible, Florian; Peter, Boris
Abstract: Im Windschatten der Digitalisierung hat sich ein Trend zu einer präzisen Regelung und Normierung einzelner Planungsschritte entwickelt – weg von einem Werksverständnis, bei dem der Werkerfolg im Vordergrund steht und die Planungsmethode selbst den Planern überlassen ist. Nach einer Umfrage des DIN 2017 haben ca. 85 % der Befragten die Entwicklung neuer Normen als „sehr dringend" oder „dringend" eingestuft. Diese Normen werden den Planungsteams in Zukunft die Planungsmethode vorgeben. Gerade die freiberuflichen Planer müssten sich an der Ausgestaltung dieser Normen und der damit verbundenen Frage „Wie wollen wir in Zukunft planen?"stärker beteiligen. Für den Flughafen in Shenzhen, die Nachhallgalerie der Staatsoper Unter den Linden in Berlin, den mehrgeschossigen Holzbau The Cradle in Düsseldorf und die neue Elefantenwelt in Stuttgart hat das Büro Knippers Helbig mit seinen Planungspartnern projektspezifische Prozessketten entwickelt, die nicht normativ erfassbar sind. Abstract: Free choice – the project determines the planning method In the wake of digitalisation, a trend towards precise regulation and standardisation of individual steps has developed, far removed from an understanding of working in which the success of the work is paramount, and where the planners themselves decide upon the actual planning method. According to a survey carried out by DIN in 2017, around 85 % of those questioned rated the development of new standards as either "very urgent" or űrgent". In future, these standards will dictate to planning teams how they must undertake their planning work. Freelance planners in particular need to play a more active role in the shaping of these standards, along with the related question: "How would we like to plan in future?". For Shenzhen airport, the 'Nachhallgalerie' at the Berlin State Opera, the multistorey timber construction 'The Cradle' in Düsseldorf and the new 'Elephant World' in Stuttgart, the Knippers Helbig practice, together with its planning partners, has developed project‐specific process chains that cannot be recorded normatively. This shows how important it is that, in future too, planners retain the freedom to help shape the processes.